Influence E-Word of Mouth Marketing, Internet Marketing and Social Media Marketing Regarding Student Decisions Choosing Stikom Prosia - Fransiska Fransiska; Ridzki Rinanto Sigit (Peneliti.net, 2023)
The study is aimed at knowing the impact of marketing communication that it consists of e-word of mouth marketing, Internet marketing, and social media marketing to the student's decision to select prophylactica research using a quantitative approach. In this study used 23 samples by sampling techniques with saturated sampling techniques. The method of dat used is a linear regression analysis using the IBM SPSS program 25. Studies indicate that all three free variables simultaneously amount to (73.2%) of the student decision selecting proxia, while partially only social media marketing affects the student's choice STIKOM PROSIA